Effects of Chitosan Oligosaccharides on Human Blood Components - Guo, Xi; Sun, Tong; Zhong, Rui; Ma, Lu; You, Chao; Tian, Meng; Li, Hao; Wang, Chengwei (Frontiers in Pharmacology, 2018)
Chitosan oligosaccharide (COS) is known for its unique biological activities such as anti-tumor, anti-inflammatory, anti-oxidant, anti-bacterial activity, biological recognition, and immune enhancing effects, and thus continuous attracting many research interests in drug, food, cosmetics, biomaterials and tissue engineering fields. In comparison to its corresponding polymer, COS has much higher absorption profiles at the intestinal level, which results in permitting its quick access to the blood flow and potential contacting with blood components. However, the effects of COS on blood components remain unclear to date. Herein, two COS with different molecular weight were characterized by FTIR and 1H NMR, and then their effects on human blood components, including red blood cells (hemolysis, deformability, and aggregation), coagulation system (activated partial thromboplastin time (APTT), prothrombin time (PT), thrombin time (TT), and the concentration of fibrinogen (Fib)), complement (C3a, and C5a activation), and platelet (activation, and aggregation), were comprehensively studied. In the case of red blood cells, COS exhibited a low risk of hemolysis in a dose and molecular weight dependent manner and the irreversible aggregation was observed in their high concentration. For coagulation system, COS has a mild anticoagulation activity through blocking the intrinsic coagulation pathway. In addition, COS showed no effect on complement activation in C3a and C5a and on platelet activation while inhibition of platelet aggregation was evident. Finally, the mechanism that effects of COS on blood components was discussed and proposed.